Effect of individual psycho-education on self-determination among opiate-dependent in methadone treatment: a randomised controlled trial - Engku Kamarudin, Engku Mardiah; Amin, Aizan Sofia; Shafie, Amin Al Haadi; Lee, Wei Rong (Gokmen Arslan, 2022)
Self-determination is a useful concept for analysing individual experiences with internal controls and demonstrates the critical role of self-determined motivation in addiction treatment. This study was designed to evaluate the effect of individual psycho-educational treatment based on integrated self-awareness and self-determination theories (i-SEAZ) toward self-determination among opiate-dependent patients in Methadone Treatment (MT). 75 methadone patients from five methadone clinics were randomly assigned to the experimental (n=38) or control (n=37) groups. Ten individual i-SEAZ sessions were administered to the experimental group, while the control group received only MT. The Treatment Motivation Questionnaire (TQM) was used to evaluate the effect of self-determination on four sub-constructs: External Motivation, Internal Motivation, Treatment Confidence, and Seeking Help. The evaluation was performed twice, once before (as a pretest) and once after (as posttest). The experimental group demonstrated a significant increase in self-determination. However, sub-construct analyses revealed that External Motivation improved significantly, but not Internal Motivation, Treatment Confidence, or Seeking help. Thus, the i-SEAZ appears to significantly improve self-determination, particularly in opiate-dependent patients. More research is needed to determine the efficacy of i-SEAZ in other drug treatment modalities. This study aims to increase counsellors' use of evidence-based treatments such as i-SEAZ in order to increase self-determination among opiate-dependent Methadone patients.